(untitled) (American Journal of Islam and Society, 2009)
This survey of the history of Iranian civilization from ancient times to the present is intended for general audiences with little knowledge of Iranian history. The book’s nine chapters consist largely of chronological presentations of political history, but occasionally make room for sections on religious movements, society, and the arts. The first two chapters briskly cover the ancient period through the Sassanids. The third runs from the Islamic conquests through the fifteenth century and contains a long section on the evolution of Persian verse tradition. The fourth and fifth chapters cover the Safavids’ rise and fall, the development of early modern Twelver Shi`ism, and the tumultuous period leading up to the Qajars. The sixth surveys the late Qajar period and the constitutional revolution, while the last three chapters detail the events of the twentieth century with an emphasis on the 1979 Islamic revolution and what has happened since. As nearly a third of the book deals with the twentieth century, the treatment of the ancient periods and the first millennium of the Islamic era are comparatively spare. Axworthy’s main project is to trace the history of a sense of “Iranianness” or “Irananian identity” that he claims to have identified in ancient sources and uses to justify composing what he calls “a history of Iran.” Although he does not provide an explicit and comprehensive definition of this “Iranian identity,” he states clearly that he is not describing a sense of nation (pp. xv-xvi and 117). Rather, he implies that this identity is a loose sense of affiliation based on the idea of a common land, language, and shared memory. But when he speaks, for example, of an “Iranian revival” in the second century or an “Iranian reconquest” in the fourteenth, he uses the very nation-centered paradigm of history that he seeks to avoid, even if he refrains from invoking a “national” sensibility ...